Analyzing Engagement of Outsource Employee Study. Case: PT Bravo Humanika Perkasa - Putra, Anugrah Nindya; Welly, John (Journal of Business and Management, 2015)
Abstract- Every organization has employees who work for them and build a connection with it. The longer employees work for an organization, the more they commit to the organization itself. This commitment that employee have can become the engagement for them. In PT Bravo Humanika Perkasa, there are a permanent employee with the agreement, and there are outsource employee. Outsourcing is not new in Indonesia, and the development is so high. But, even with the high development outsourcing in Indonesia, there are still many problems that have been seen. So this study aims to analyse the engagement of outsource employee in PT Bravo Humanika Perkasa. The sample used in this study is simple random sampling in the Jakarta, Bekasi, Tangerang, and Depok area with total respondents to 100 people. To see the relationship of independent variables on the dependent variable, multiple linear regression method is used. This result of this research is performed that consist of 11 variables which affect the engagement. From 11 variables, there are 3 variable with a very strong relationship with the level of employee engagement. Then there is an equation result from the regression method that used.Â Keywords: engagement, PT Bravo Humanika Perkasa, Outsource employee, multiple linear regression,Â